Stability of peptide amides under high pressure - Corrales Moreno, Margarita; Fernández, Avelina; Butz, Peter; Stärke, Joachim; Pfaff, E.; Wiesmüller, K. H.; Tauscher, Bernhard (High pressure research, 2007)
The effects of pressure on two-model peptide amides have been analysed since the modifications in those groups are usually related to changes in protein/peptide functionality. Pressure accelerated the hydrolysis at the C-terminal amide of the dipeptide H-Leu-Gly-NH2, producing the diketopiperazine cLG that might have a biological role. Furthermore, pressure accelerated the deamidation of the asparagine residue in the oligopeptide H-Val-Pro-Gly-Val-Gly-Asn-Gly-Val-Pro-Gly-Val-Gly-OH containing an Asn-Gly sequence, probably via a cyclic imide intermediate, producing a peptide with aspartic acid. The reported pressure-induced modifications in amide groups were slow under the considered conditions (600-800 MPa, 60-80 °C). Effects under parameters closer to pressure-assisted thermal sterilization remain to be investigated.
Gesehen am 08.01.2024